Humanização da pena de prisão: uma possibilidade real? - Santos, Silmara Mendes Costa (2007)
The objective of this work was to show to the possibilities and the limits of the humanizes of the punishment by confinement in this effective social order. For this, we leave of the understanding of the articulated social reality with the totality. Thus, we could understand the origin and the nature of the punishment by confinement, considering questions as: the humanizes concepts that do not reach the prisoner system neither and nor the society, exactly when the arrest passes for some reforms with the intention of being humanized; the prisoner reality, that does not diminish the crime tax nor obtains to correct the illegalities practiced for the agents of the State; that it does not reach the possibility of Been criminal treatment considered by the proper one; that it produces greater crime and it contributes for the increase of the social problems. To reach such objectives, our work had as theoretical base the marxiana perspective, whose starting point is the man, natural, social, alive human being, concrete, that acts conscientiously. From the beddings elaborated for Marx, we could point that the origin of the man is in the work, then the man depends on its interchange with the nature to satisfy its necessities and if to constitute socially. The gotten data disclose, among others aspects, that: the sociability form is desman in its essence, therefore the man to survive vended its force of work, being explored to generate the accumulation of the capital; the condition human being is produced by men whom if they differentiate its access to the private property; the social relations of production determine the sprouting of the arrest; the social function of the arrest nothing more is of what adjusting the man to the society, of coercitive and repressive form, segregating the villains and the poor persons; the control of the crime for the State and the Right is the half concrete to protect the interests of the capitalist society; the law and the crime only confirm the ideology that supports effective economic and social the order, serving of instrument of domination for the biggest development of the productive forces; the proposal of prisoner humanizes in the Brazilian legislation not even obtains to be fulfilled: the punishment by confinement does not obtain to diminish the incidence of the crime. We conclude that, ahead of this understanding of the social reality, the arrest, exactly with as many reforms, it is far from being a humanized environment. Soon, the construction of a criminal system humanized and a society fully joust passes for the conscientious domain of the process of the auto-construction human being.